Penta- and Tetra-cyclic Triterpenoids from Aglaia cucullata Stembark and Cytotoxicity against Cancer and Normal Cells - Kindi Farabi; Wahyu Safriansyah; Desi Harneti; Hadi Kuncoro; Sofa Fajriah; Unang Supratman (Journal of Mathematical and Fundamental Sciences, 2025)
Three triterpenoid compounds, belonging to the penta- and tetracyclic groups, were successively isolated from the stembark of Aglaia cucullata and identified as b-amyron (1), dammaradienon (2), and cabralealactone (3). After extensive extraction, chromatographic separation and purification, compounds 1 to 3 were gained. Spectroscopic analysis in addition to HRMS, FTIR, 1D and 2D NMR analysis were utilized to determine the chemical structure. After that, compounds 1 to 3 were tested against breast cancer, melanoma as well as normal kidney cells (MCF-7, B16-F10, and CV-1, respectively). The resulted cytotoxicity test revealed that compound 1 had the best cytotoxicity against all cells compared with the other isolated compounds. This result suggests that the pentacyclic triterpenoid core in compound 1 increases cytotoxicity compared with a tetracyclic skeleton.